KURANGNYA MINAT PENGGUNAAN BAHASA LAMPUNG PADA ZAMAN SEKARANG DI KALANGAN ANAK MUDA. - Putra, Yudha; Zalna, Ismiatul Laili (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study examines the phenomenon of declining interest in using the Lampung language among the younger generation in the modern era. The aim of this study is to uncover the reasons why young people rarely use Lampung in their daily lives, identify the contributing factors, and understand the long-term impact if this regional language is no longer used by the next generation. The research method used is qualitative descriptive and observation of the language behavior of the Lampung community. The results indicate that the dominance of Indonesian and foreign languages ​​in education, media, and social environments, along with the minimal use of Lampung in families and schools, are the main causes of this decline. This condition has the potential to lead to the extinction of the Lampung language, which will impact the loss of cultural heritage and ethnic identity of the Lampung people. Therefore, concrete steps are needed from various parties, such as language revitalization in education, the use of digital media, and increasing awareness of regional language preservation, so that Lampung can continue to be preserved and used by the younger generation.